Investigation of the Microstructure and Mechanical Properties of Si-Al-N Transparent Coatings; Key Engineering Materials; Vol. 683 : Multifunctional Materials: Development and Application - Bozhko I. A. Irina Aleksandrovna; Rybalko E. V.; Fedorishcheva M. V. Marina Vladimirovna; Vorobiev Y. A.; Magzhanov R. M.; Chernyavsky A. G.; Sergeev V. P. Viktor Petrovich (Physicochemical Properties of Materials and Current Processing Technologies, 2016)
Title screen